The clinical characteristics and treatment of pertussis patients in a tertiary center over a four-year period - Bayhan, Gülsüm İclal and Tanır, Gönül and Nar-Otgun, Selin and Aydın-Teke, Türkan and Metin-Timur, Özge and Öz, Fatma Nur (The Turkish Journal of Pediatrics, 2012)
We performed a retrospective study of pertussis patients seen during the period July 2007-December 2011. All patients were microbiologically confirmed through polymerase chain reaction (PCR) or culture. Thirty one patients with positive Bordetella spp. culture or PCR were identified, with a median age of two months. Seventeen patients had received no pertussis vaccination. The most frequent symptoms were paroxysmal cough (100%) and cyanosis (87.1%). The mean duration of the symptoms prior to admission was 12.8 ± 8.0 days. Leukocytosis and thrombocytosis were detected in 64.3% and 67.9% of the 28 hospitalized patients, respectively. Erythromycin had been given to eight patients and clarithromycin to 23 patients. The mean hospital stay was 9.5 ± 5.5 days (range: 3 to 28 days). No patients were readmitted or died. We believe that patients with characteristic paroxysmal cough with cyanosis but no fever should alert clinicians to the possibility of pertussis, and they should be treated without delay. PCR assay provided additional benefit in the diagnoses of the study patients.